Joan Fuster y Julián Mariás : dos intelectuales frente a la transición española a la democracia - Rodríguez Milán, Roberto (Acta Hispanica, 2015)
From autumn 1975 onwards, political change becomes a tangible possibility in Spain. In the face of a quite unpredictable scenario for the Iberian country, filled with concerns, uncertainties and expectations, many intellectuals take a step forward in what they regard as their social role, attempting to engage a dialogue with the society they belong to by proposing a personal reading of the political and social reality of the time. We highlight here the dissimilar prominence of two intellectuals, both of them veteran in their dissent versus General Franco’s dictatorship: the writer Joan Fuster and the philosopher Julián Marías. Through their constant “emergency” essays which are here under consideration, these two intellectuals intensify their effort so as to contribute to shape a public opinion informed about the past and committed with the present and the future, able to become an active subject of History once again.